2019
DOI: 10.1155/2019/3659432
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Essential Oils of Rosmarinus officinalis L. by Two Different Methods: Hydrodistillation and Microwave Assisted Hydrodistillation

Abstract: The extraction of essential oils is generally carried out by two main techniques: azeotropic distillation (hydrodistillation, hydrodiffusion, and steam distillation) and extraction with solvents. However, these traditional methods are a bit expensive, especially since they are extremely energy and solvent consuming. This work consists in studying two methods of extraction of the essential oils of Rosmarinus officinalis L.: microwave assisted hydrodistillation (MAH) and Clevenger hydrodistillation (CH). Several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(106 citation statements)
references
References 21 publications
1
97
2
6
Order By: Relevance
“…[56] O. vulgare is one of the main species of this genus and then the most studied, however, other minor species show interesting chemical composition associated with biological activities, for example a study of the chemical characterization and the evaluation of antimicrobial, enzyme inhibitory, and antioxidant activities of methanol and water extracts of Turkish O. onites has been recently reported. [424] In total 28 components belonging to polyphenols, flavonoids, terpenoids, organic acids and esters have been identified: 3-O-(4-coumaroyl)quinic acid (16), acacetin (17), cirsimaritin (14), naringenin (9), tuberonic acid glucoside (18), ferulic acid (3), apigenin-7,4'-dimethyl ether (19), azelaic acid (20), baicalin (21), casticin (22), cirsiliol (11), dihydrorobinetin (23), gardenin B (24), genkwanin (25), isoferulic acid (26), kaempferol (27), nevadensin (28), oroxylin A 7-O-glucuronide (29), quercetin (30), rosmarinic acid methyl ester (31), sakuranetin (32) and salvigenin (33).…”
Section: Oreganomentioning
confidence: 99%
See 1 more Smart Citation
“…[56] O. vulgare is one of the main species of this genus and then the most studied, however, other minor species show interesting chemical composition associated with biological activities, for example a study of the chemical characterization and the evaluation of antimicrobial, enzyme inhibitory, and antioxidant activities of methanol and water extracts of Turkish O. onites has been recently reported. [424] In total 28 components belonging to polyphenols, flavonoids, terpenoids, organic acids and esters have been identified: 3-O-(4-coumaroyl)quinic acid (16), acacetin (17), cirsimaritin (14), naringenin (9), tuberonic acid glucoside (18), ferulic acid (3), apigenin-7,4'-dimethyl ether (19), azelaic acid (20), baicalin (21), casticin (22), cirsiliol (11), dihydrorobinetin (23), gardenin B (24), genkwanin (25), isoferulic acid (26), kaempferol (27), nevadensin (28), oroxylin A 7-O-glucuronide (29), quercetin (30), rosmarinic acid methyl ester (31), sakuranetin (32) and salvigenin (33).…”
Section: Oreganomentioning
confidence: 99%
“…For the above mentioned reasons, several studies were conducted in the recent past with the aim to optimize or increase the yields of EOs using novel techniques in addition or as ‘pre‐treatments’ of the traditional way of production. Examples of these novel techniques are microwave‐assisted hydrodistillation, solvent‐free microwave extraction, ultrasounds, ultrasonic‐microwave assisted preceded by enzymolysis . From these studies, it emerges that the combination of advanced and traditional techniques leads to a variable increase in yields and a significant reduction in times with consequent energy savings.…”
Section: Essential Oils: Very Old ‘Guys’ With Great Prospectsmentioning
confidence: 99%
“…Our results are supported by Bouyahya et al [31], who reported eucalyptol (23.673%), camphor (18.743%), borneol (15.46%), and α-pinene (14.076%) as the major chemical components of the REO. In addition, Elyemni et al [32] reported the presence of eucalyptol (32.18%), camphor (16.20%), α-pinene (15.82%), camphene (9.16%), and α-terpineol (7.36%) in the chemical composition of the REO. Based on these studies, our essential oil exhibits a chemical composition commensurate to those reported by other authors who presume its memory-enhancing and antioxidant activity.…”
Section: The Chemical Composition Of the Essential Oilmentioning
confidence: 99%
“…Su aceite esencial y extractos son antimicrobianos con propiedades antioxidantes (Basheer, 2018), anti-nefrotóxicos, antiinflamatorios, antitumorales, anti-hepatotóxicos (El-Desouky et al, 2019), antihelmínticos (Zoral et al, 2018), anticancerígenos (Karim et al, 2017), antifúngicos (Ebrahimi et al, 2020), insecticidas, antidiabéticos, antimutagénicos, anti-toxigénicos (Nieto et al, 2018), citotóxicos, analgésicos, herbicidas, hipoglucémicos, hipolipemiantes (Karadağ et al, 2019), antiartríticos (Beltrán et al, 2017), antidepresivos, antiobesidad, neuroprotectores (Hamidpour, Hamidpour & Elias, 2017), antihiperglucémicos, antihiperlipidémicos (Ali et al, 2019), antidiarreicos (Selmi, Rtibi, Grami, Sebai & Marzouki, 2017) e inhibidoreres de la germinación de semillas (Sadeh et al, 2019), efecto inhibidor contra el VIH (Barbieri et al, 2019), vasorrelajantes (Zhang et al, 2019), antivirales (Sumintarti et al, 2018), antitrombóticos (Elyemni et al, 2019), hipouricémicos, proapoptóticos (de Oliveira et al, 2019), anti-infecciosos, espasmolíticos (Gomes et al, 2020), entre otros más.…”
Section: Romero (R Officinalis L)unclassified
“…El romero posee alrededor de un 0.5-2.5% de aceite esencial, conformado en su mayor parte por 1,8-cineol (15-50%), alcanfor (15-25%), α-pineno (10-25%), canfeno (5.2-8.6%) y borneol (3.2-7.7%) (Sumintarti et al, 2018). El aceite esencial de mayor calidad es obtenido de sus hojas, donde se encuentra la mayoría de las tricomas glandulares que lo secretan (Elyemni et al, 2019).…”
Section: Metabolitos Secundarios Del Romero (R Officinalis L)unclassified